Haplotype analysis of DXS548 and FRAXAC1 microsatellite loci in Iranian patients with Fragile X Syndrome - Aleyasin, seyed ahmad; Salamat, Fatemeh; Mirakhori, Mojgan (Iranian Journal of Child Neurology, 2018)
Objective Fragile X syndrome (FXS) is the most common cause of inherited mental retardation caused by expansion of a (CGG) repeat region up to 1000 repeat in 5' region of the FMR1 gene located in FRAXA locus Xq27.3. To better understand the mechanism involved in expansion of CGG region, the molecular characteristic of the flanking microsatellite markers in the region must be clarify in different populations. This study has aimed to examine the potential association between specific haplotype and the expanded AC-repeat region in cases and controls chromosomes. Materials & methods Forty unrelated FXS males and 62 unrelated normal males originating from various regions of Iran were haplotyped by analyzing two CA-repeat markers, FRAXAC1 and DXS548. Results Significant linkage disequilibrium was obtained between DXS548 and FRAXAC1 specific marker alleles and CGG repeat expansion among 40 fragile X cases compared to 62 normal controls. The frequencies of DXS548 and FRAXAC1 longer alleles in patients are significantly higher than that in control group. Two FRAXAC1 long alleles were only observed in cases, possibly due to concatenated mutations. The increase of heterozygosities in fragile X cases (DXS548 78.6%, FRAXAC1 64.6%) in comparison to the controls (DXS548 63.0%, FRAXAC1 47.0%) showed a multimodal distribution of fragile X associated alleles. Conclusion Haplotype analyses with DXS548 and FRAXAC1 markers represented that haplotype distribution in the normal controls and FXS patients were significantly different, representing a weak founder effect. Keywords: FXS; DXS548; FRAXAC1; haplotype